KARAKTERISTIK HABITAT MIKRO SEBAGAI DASAR POLA PENETASAN TELUR MALEO DI TAMAN NASIONAL LORE LINDU SULAWESI TENGAH - Hafsah Hafsah; Tri Yuwanta; Kustono Kustono; Djuwantoko Djuwantoko (Agroland: Jurnal Ilmu-ilmu Pertanian, 2008)
The Objective of the study was to identify microhabitat characteristics in natural nesting ground as a basic form of egg hatching of maleo birds for ex-situ habitat in Lore Lindu National Park. Survey methods and experimental design were applied in this study using Saluki Nesting Ground as a habitat model. In a natural habitat, variables observed were microclimate condition (temperature and humidity, depth and diameter of holes) while in an artificial habitat where four different forms of eggs hatching (in-situ, ex-situ, incubator by means of media rack and sand) were applied temperature, humidity, hatching quality, incubation time, hatching weigh, and mortality were determined. Data analysis applied was descriptive analysis and multivariate test using SPSS computer program. Results of the study showed that in the natural nesting ground the temperature ranged from 30 to 35 oC with an average temperature of 33.03oC, and the humidity from 60.20 to 71.10% with an average humidity of 68.55%. The hole diameter ranged from 28-63 cm with an average hole diameter of 41.64 cm and the hole depth from 51-87cm with an average hole depth of 63.29 cm. The application of hatching method was resulted in the in-situ temperature and humidity of 32.90 oC and 68.41%, respectively, and the ex-situ of 31.68 oC and 67.52%, respectively, rack incubator of 33.99 oC and 70.06%, respectively, and sand incubator of 33.78 oC and 71.02%, respectively. The longest incubation time was found in the ex-situ semi natural hatchery which was 78.40 days, followed by the in-situ habitat 63.48 days, rack incubator 59.40 days, and sand incubator 59.33 days. The best hatching quality was found in the rack incubator, but the mortality rate was highest. The application of incubator for egg hatching of maleo birds could reduce the incubation time length and increase the hatching quality